2006
DOI: 10.1161/circulationaha.105.000588
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Capability of Circulating Progenitor Cell to Differentiate on Myocardial Salvage in Patients With Primary Acute Myocardial Infarction

Abstract: Background-Circulating endothelial progenitor cells (EPCs) are known to be involved in vasculogenesis and mobilized after acute myocardial infarction (AMI). To test the hypothesis that the angiogenic function of EPCs affects post-myocardial infarction (MI) myocardial salvage, we evaluated the number and potential differentiation of EPCs and compared these data with clinical parameters 6 months after MI. Methods and Results-Consecutive 51 patients (age, 61Ϯ8 years, meanϮSD) with primary AMI who were successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 22 publications
3
59
0
3
Order By: Relevance
“…3,8,10 Moreover, not only the number of EPCs, but also their capability to differentiate into adult endothelial cells may affect functional improvement and infarct size reduction evidenced by nuclear scan, left ventricular ejection fraction salvage and favorable remodeling in patients with AMI. 47 The mobilization of EPCs 24 h after acute MI showed significant positive correlation with extent of viable ischemic myocardium, but not with infarct size and microvascular obstruction. This supports the hypothesis that myocardial ischemia, and not necrosis, is a pivotal determinant of EPCs release from the BM.…”
Section: Mobilization Of Spcs and Clinical Outcomes In Acute Coronarymentioning
confidence: 88%
“…3,8,10 Moreover, not only the number of EPCs, but also their capability to differentiate into adult endothelial cells may affect functional improvement and infarct size reduction evidenced by nuclear scan, left ventricular ejection fraction salvage and favorable remodeling in patients with AMI. 47 The mobilization of EPCs 24 h after acute MI showed significant positive correlation with extent of viable ischemic myocardium, but not with infarct size and microvascular obstruction. This supports the hypothesis that myocardial ischemia, and not necrosis, is a pivotal determinant of EPCs release from the BM.…”
Section: Mobilization Of Spcs and Clinical Outcomes In Acute Coronarymentioning
confidence: 88%
“…18 Another study of AMI patients reported that the number of mobilized EPCs in the peripheral blood and the potential of those EPCs to differentiate into endothelial cells correlated with greater myocardial salvage, decreased end-systolic volume, and increased EF recovery 6 months after AMI. 24 Based on these reports, the main contribution of CD34 + cells and EPCs to AMI is considered neovascularization. [17][18][19] In animal models other than AMI, Muse cells have been shown to home into damaged tissue and differentiate spontaneously into cells compatible with the tissue they targeted and repair damaged tissue.…”
Section: Remodeling and Muse Cell Numbermentioning
confidence: 99%
“…A limited but growing number of follow-up studies involving MSCs have been reported since, most aimed at taking advantage of the plasticity of MSCs to treat a disease. These clinical studies (Table 3) have demonstrated promising results in treating patients with cancer, in reducing the incidence of GVHD after bone marrow transplantation, in promoting heart tissue recovery from massive myocardial infarction, in improving the recovery of patients after amyotrophic lateral sclerosis, and in treating fatal disorders such as metachromatic leukodystrophy and Hurler syndrome (47,(51)(52)(53). At the time of this Perspectives in Diabetes article's submission, ϳ32 clinical trials involving administration of MSCs were listed at http://www.ClinicalTrials.gov, each potentially seeking to exploit the immunomodulatory properties of MSCs to achieve their desired therapeutic goal.…”
Section: Fig 1 Schematic Representation Of Plausible Mechanisms By mentioning
confidence: 99%